Canadian Rural Women's Experiences with Rural Primary Health Care Nurse Practitioners - Beverly D Leipert; Jessica Wagner Delaney; Dorothy Forbes; Cheryl Forchuk (Rural Nurse Organization; Binghamton University, 2011)
Background: In Canada, one in five women lives in a rural area. These rural women often experience different health challenges than urban women, including lower life expectancy, higher rates of disability and cancer, fewer available health care resources and greater distances to access health care services. Nurse practitioners [NPs] provide important primary health care [PHC] services to rural women. Research Objective: The purpose of this research study was to explore rural women's experiences with primary health care nurse practitioners [PHCNPs]. Method and Sample: In-depth, face-to-face interviews using interpretive description methodology were conducted with nine rural women, aged 18-80, who used NP services in rural southwest Ontario, Canada. Results: The participants in the study particularly appreciated the nursing knowledge of the NP, the time the NPs spent with them, and the thoroughness of the care provided by NPs. These foundational elements of the participants' experiences with rural NPs created a sense of trust and respect, which lead to a collaborative partnership between the NP and the rural women. Conclusions: Results of this study suggest that these rural women were overwhelmingly satisfied with the care provided by NPs. In particular, they valued the collaborative partnership with the NP. These findings have important implications for rural health care practice, policy, and education.